Biological Subtypes and Distant Relapse Pattern in Breast Cancer Patients After Curative Surgery (Study of Anatolian Society of Medical Oncology) - (:unkn) unknown (KARGER, 2016)
Purpose: The aim of the study was to investigate the association between the molecular subtypes and patterns of relapse in breast cancer patients who had undergone curative surgery. Methods: We retrospectively evaluated 1,350 breast cancer patients with relapses after curative surgery between 1998 and 2012 from referral centers in Turkey. Patients were divided into 4 biological subtypes according to immunohistochennistry and grade: triple negative, HER2 overexpressing, luminal A and luminal B. Results: The percentages of patients with luminal A, lumina! B, HER2-overexpressing, and triple-negative breast cancer were 32.9% (n = 444), 34.9% (n = 471), 12.0% (n = 162), and 20.2% (n = 273), respectively. The distribution of metastases differed among the subgroups: bone (66.2% and 53.9% in lumina! A and B vs. 38.9% in HER2-overexpressing and 45.1% in triple negative, p < 0.001), liver (40.1% in HER2-overexpressing vs. 24.5% in lumina! A, 33.5% in luminal B, and 27.5% in triple negative, p < 0.001), lung (41.4% in triple negative and 35.2% in HER2-overexpressing vs. 30.2% and 30.6% in luminal A and B, p = 0.008) and brain (25.3% in HER2overexpressing and 23.1% in triple negative vs. 10.1% and 15.1% in lumina! A and B, p < 0.001). Conclusions: Organ -specific metastasis may depend on the molecular subtype of breast cancer. Tailored strategies against distant metastasis concerning the molecular subtypes in breast cancer should be considered. (C) 2016 S. Karger GmbH, Freiburg.
Keywords: Breast cancer; Relapse pattern; Molecular subtype; MOLECULAR SUBTYPES; PROGNOSTIC-FACTORS; METASTASIS; RECURRENCE; SURVIVAL; WOMEN; RISK; ESTROGEN; GENES; SITE